Influenza Viruses and mRNA Splicing: Doing More with Less - Julia Dubois (American Society for Microbiology, 2014)
ABSTRACT During their nuclear replication stage, influenza viruses hijack the host splicing machinery to process some of their RNA segments, the M and NS segments. In this review, we provide an overview of the current knowledge gathered on this interplay between influenza viruses and the cellular spliceosome, with a particular focus on influenza A viruses (IAV). These viruses have developed accurate regulation mechanisms to reassign the host spliceosome to alter host cellular expression and enable an optimal expression of specific spliced viral products throughout infection. Moreover, IAV segments undergoing splicing display high levels of similarity with human consensus splice sites and their viral transcripts show noteworthy secondary structures. Sequence alignments and consensus analyses, along with recently published studies, suggest both conservation and evolution of viral splice site sequences and structure for improved adaptation to the host. Altogether, these results emphasize the ability of IAV to be well adapted to the host’s splicing machinery, and further investigations may contribute to a better understanding of splicing regulation with regard to viral replication, host range, and pathogenesis.